Accuracy of antenatal detection of serious congenital heart disease in low risk population. (7th June 2011) - Haium, A Abdul; Messenger, L; Cross, M; Muchena, B; Yates, R; Kelsall, W
Abstract : Objective: The purpose of this study was to evaluate the accuracy of antenatal detection of serious congenital heart disease (SCHD) in a low risk population. Study design: An ongoing prospective descriptive study over a period of 13 years. Patients were identified from local obstetric, neonatal and paediatric cardiac databases. Details of all suspected fetal SCHD detected during routine antenatal ultrasound anomaly scans by the ultrasonographers were prospectively recorded and all suspicious pregnancies were referred for specialist fetal echocardiography. All postnatal diagnoses were confirmed by echocardiography by paediatrician with expertise in cardiology or Paediatric cardiologist. Results: During the study period from 1997 to 2009 there were 64681 births; over this 13-year period total of 199 children with SCHD were identified, of which 131 cases were suspected antenatally and 68 infants were diagnosed postnatally. In the antenatal subgroup termination of pregnancy was performed in 40 (31%) cases, in-utero death occurred in 6 (5%) cases. 80 (63%) were with isolated cardiac anomalies and 47 (37%) had other associated structural and/or chromosomal abnormalities. Abnormal karyotype was present in 27 (21%) cases. The overall antenatal detection rate was 66% (95% CI 61 to 75). The overall incidence of SCHD was 3.2/1000 live births. There was an overall survival rate of 64% at birth following antenatal diagnosis of SCHD. Conclusions: With adequate training, high-resolution equipment and sufficient scanning time, high detection rates of SCHD can be consistently achieved in low risk population.